Revision of Nearctic Nephrocerus Zetterstedt (Diptera: Pipunculidae) - Skevington, Jeffrey H. (Zootaxa, 2005)
The Nearctic species of Nephrocerus Zetterstedt, 1838 are revised and include two described species, N. daeckei Johnson, 1903 and N. slossonae Johnson, 1915, and four new species: N. acanthostylus spec. nov., N. atrapilus spec. nov., N. corpulentus spec. nov. and N. woodi spec. nov. A key to species is provided and diagnostic characters, including male and female genitalia, are illustrated. Nephrocerus is recorded for the Neotropical Region for the first time.